Notary Liability for Making Assets Based on False Letters Delivered by Company - Muhamad Ridho (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
This study aims to determine the obstacles of the notary in identifying the truth of the letter or document submitted by the tappers. The type of research used in this research is juridical empirical research, which is research that is carried out by examining the applicable legal provisions and what happens in society. This research approach method is a sociological and statutory approach. The data in this study are library data and field research. The data were obtained from interviews and with sources, namely 03 (three) Notaries in Kendari City, and supporting data obtained through literature and document studies. The data collection techniques that the researcher will use are interviews and document studies. The results of this study indicate that the notary is only formally responsible and has no obligation to materially prove the correctness of the documents shown by the informants. Notaries can only be held accountable if the Notary is proven to have committed a violation as stipulated in Articles 84 and 85 of the UUJN and the notary's code of ethics, which can be held responsible criminally, civil and administratively. Barriers can be in the form of: dishonesty in the correctness of information and/or documents submitted; technological engineering through scanning and editing of submitted documents, client demands for resolving the deed quickly, lack of extracting information/information from the notary to the parties; the high quantity of notary work which causes inaccuracy in making deeds, and the emotional closeness of the notary to the tappers. Legal protection for notaries in carrying out their positions in relation to the correctness of documents submitted by the tappers includes: Preventive Legal Protection, namely: Notaries carry out their positions by always referring to statutory regulations and the notary's code of ethics; Supervision and routine examination of the notary honor council. Meanwhile, repressive legal protection, namely: legal protection for notaries in the event of a case or party reporting a notary on an alleged violation of the law in a deed made with the approval of the Notary Honorary Council which is for the benefit of judicial proceedings, investigations of public prosecutors or judges with the approval of the Notary Honorary Council.